The Role of Milk Protein and Whey Permeate in Lipid-based Nutrient Supplements on the Growth and Development of Stunted Children in Uganda: A Randomized Trial Protocol (MAGNUS). Issue 5 (24th April 2021) - Pesu, Hannah; Mutumba, Rolland; Mbabazi, Joseph; Olsen, Mette F; Mølgaard, Christian; Michaelsen, Kim F; Ritz, Christian; Filteau, Suzanne; Briend, André; Mupere, Ezekiel; Friis, Henrik; Grenov, Benedikte
ABSTRACT: Stunting is associated with cognitive impairment and later chronic disease. Previous trials to prevent stunting have had little effect, and no trials seem to have provided larger amounts of energy and high-quality proteins to already stunted children. We aimed to assess the effects of milk protein (MP) and whey permeate (WP) in large-quantity lipid-based nutrient supplements (LNS-LQ), among stunted children, on linear growth and child development. This was a randomized, double-blind, 2-by-2 factorial trial. Stunted children aged 12–59 mo from eastern Uganda ( n = 750) were randomly assigned to receive 100 g LNS-LQ with or without MP and WP ( n = 4 × 150) or no supplement ( n = 150) for 3 mo. The primary outcomes were change in knee-heel and total length. Secondary outcomes included child development, body composition, anthropometry, and hemoglobin. Micronutrient status, intestinal function, and microbiota were also assessed. Our findings will contribute to an understanding of the role of milk ingredients and LNS in linear catch-up growth. This trial was registered at www.isrctn.com as ISRCTN13093195. Abstract : Will large quantity lipid-based nutrient supplements containing milk protein and whey permeate improve linear growth as well as body composition, gut function, and child development in stunted children?